Pathology of the Ovary, Fallopian Tube and Peritoneum - Wilkinson, Nafisa (Essentials of Diagnostic Gynecological Pathology, 2014)
As the second volume in the Essentials of Diagnostic Gynecological Pathology series sponsored by the British Association of Gynecological Pathologists, Pathology of the Ovary, Fallopian Tube and Peritoneum is one of the very few dealing wholly with this subject. Pathology of the Ovary, Fallopian Tube and Peritoneum introduces the topic with a discussion of the anatomy, development, histology and normal function of the ovary, followed by chapters on non-neoplastic disorders of the ovary; surgery and medical management of ovarian cancer; and the use of imaging, frozen sections and cytology in ovarian pathology. The book then goes on to describe specific disorders of the ovary, fallopian tube and peritoneum in detail, and finishes with a chapter on specimen cut-up.   Pathology of the Ovary, Fallopian Tube and Peritoneum has been written to be useful diagnostically to general as well as specialist gynecological histopathologists and pathologists in training.  Gynecologists, oncologists, genitourinary physicians and cancer nurse specialists will find expert insights here that will help in treatment and counselling of their patients.